THE IMPLEMENTATION OF ACCOUNTANTS’ PROFESSIONAL CODE OF ETHICS IN DEVELOPED AND DEVELOPING COUNTRIES: A LITERATURE REVIEW - Masse, Finka Azzahra Utami; Angel, Yolanda; Bukit, Rina br (UTSAHA: Journal of Entrepreneurship, 2023)
The accounting profession has a crucial role in maintaining integrity and transparency in corporate financial reporting, which has a direct impact on investor confidence and financial market stability. Therefore, all accountants in both developed and developing countries must respect the code of ethics issued by the professional association of accountants. This research aims to compare the implementation of accounting codes of ethics in developed and developing countries to identify the differences and similarities in ethical accounting practices. This research describes the differences in the context of accounting ethics between developed and developing countries and their implications for accounting practice. In addition, this research also highlights the challenges that developing countries face in implementing the principles of accounting ethics codes and examines the opportunities for improvement in the accounting field. This research uses a qualitative descriptive approach using the literature review method. This research identifies that within the past years, cases of violating the professional code of ethics of accountant have occurred in both developed and developing countries. Every accountant, whether in developed or developing countries, is expected to adhere to these principles in their practice. Furthermore, implementing these principles is essential to maintaining public trust and the sustainability of the accounting profession.